The association of beliefs about medicines with medication adherence and glycemic control among patients with type 2 diabetes: a cross-sectional survey - Li, Haiyan; Wang, Nannan; McIver, David J.; Zhang, Lu; Shi, Junfei; Liu, Dongwei; Min, Hui (Frontiers in Endocrinology, 2026)
BackgroundBeliefs about medicines have been identified as important determinants of medication adherence for multiple chronic diseases such as hypertension, diabetes, and asthma. This study aimed to examine the association of beliefs about medicines with medication adherence and glycemic control among patients with type 2 diabetes (T2D) in Xi’an, China.MethodsA cross-sectional study was conducted with T2D patients recruited from two large tertiary hospitals in Xi’an, China, from August 1, 2024 to March 31, 2025. The Beliefs about Medicines Questionnaire (BMQ) was used to assess patients’ beliefs about hypoglycemic agents, and the Adherence to Refills and Medications Scale in Diabetes (ARMS-D) was used to assess adherence to hypoglycemic agents. The recommended cut-off of HbA1c<7.0% was used as an indicator of glycemic control. Logistic regression analyses were performed to investigate the determinants of both medication adherence and glycemic control. Receiver operating characteristic (ROC) analyses were conducted to assess the performance of the logistic regression model in predicting adherence to hypoglycemic agents.ResultsOf these 446 patients enrolled in the study, the overall medication adherence was 32.5%, while 30.5% of patients achieved adequate glycemic control (HbA1c <7.0%). Multivariable logistic regression analyses revealed that patients who expressed stronger concern beliefs about the medicine had 1.20 (95% CI = 1.130-1.264) and 1.08 (95% CI = 1.022-1.136) times greater odds of non-adherence to hypoglycemic agents and inadequate glycemic control, respectively, than those expressed weaker concern beliefs, while necessity beliefs about the medicine were significantly negatively associated with medication non-adherence (adjusted OR 0.873 [0.814, 0.936]; p<0.001) and inadequate glycemic control (adjusted OR 0.916 [0.853, 0.983]; p = 0.015). This study found that presence of comorbidities and longer duration of diabetes (>10 years) was associated with medication adherence. Diabetes duration for 5–10 years and higher income were found to be associated with glycemic control, while taking injectable hypoglycemic agents and alcohol consumption were associated with inadequate glycemic control among T2D patients.ConclusionThis study revealed the status of suboptimal glycemic control and medication adherence of patients with T2D in Xi’an. Pharmacists and nurses could play an important role in educational and behavioral intervention of patients’ beliefs about medicines.